Mycotoxin – induced apoptosis in swine kidney epithelial cells - Agnieszka Chrustek (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2016)
Apoptosis, as the programmed cell death, plays a significant role in proper functioning of an organism, both in the postnatal period and during embryogenesis. Disturbances in this process can lead to the occurrence of several dysfunctions, e.g. cancer, stroke, Alzheimer’s disease and others. Apoptosis can be triggered by factors such as oxidative stress, free radicals, UV radiation and cytotoxic drugs, but also mycotoxins, e.g. aflatoxins, ochratoxin A and trichothecenes. These toxins are produced primarily by fungi of Aspergillus, Penicillium, Fusarium and Stachybotrys genera. The aim of the study was to investigate the effect of mycotoxins on the occurrence of apoptosis in the swine kidney (SK) epithelial cells. For this purpose, trichothecene T2 toxin was used at a concentration of 2.5 µM and 25 µM, aflatoxin B1 at a dose of 10 µM and 30 µM, and ochratoxin A concentrations of 50 µM and 80 µM. The results were assessed using flow cytometer Muse Cell Analyzer (Merck). Studies have shown high sensitivity of the cell line SK on mycotoxins. Apoptosis was caused by all kinds of toxins and depended on the dose of examined substance. T2 toxin at a concentration of 2.5 µM caused apoptosis in 6.9% of the cells, whereas at a concentration of 25 µM in 26.35% of the cells. Aflatoxin B1 used at concentrations of 10 µM and 30 µM caused apoptosis in 13.5% and 40.6% of the cells, respectively. The use of ochratoxin A in concentrations of 50 µM and 80 µM caused the occurrence of apoptosis respectively in 68.51% and 60.41% of the cells.